2012
DOI: 10.7235/hort.2012.11071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cutting Condition on Growth of Rooted Cuttings and Cut Flower in Plug Cutting of Dendranthema grandiflorum 'Baekma'

Abstract: This study was carried out to examine the effect of cutting condition on the growth of rooted cuttings and their subsequent growth of cut flower in plug cutting of Dendranthema grandiflorum 'Baekma'. The more leaves were attached to the cutting, the higher shoot growth of rooted cutting was observed. Cutting with two to six leaves was effective in shoot growth and rooting than any other treatment. Shoot growth of rooted cutting was not affected by cutting length, but rooting was better in 5 to 7 cm long cuttin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…The growth of cut chrysanthemum is affected by the conditions of cuttings, which affects not only rooting but also the growth of cut chrysanthemum Jinba and Baekseon after cutting (Yoo and Roh, 2009;Roh and Yoo, 2010). When the length of Jinba cuttings was 9 cm; the number of leaves, 4~6; and diameter, 3.2 mm, the length and diameter of cut flowers were longer than other cut flowers.…”
Section: Correlation Between Cultivation Methods and The Quality Of Cmentioning
confidence: 99%
“…The growth of cut chrysanthemum is affected by the conditions of cuttings, which affects not only rooting but also the growth of cut chrysanthemum Jinba and Baekseon after cutting (Yoo and Roh, 2009;Roh and Yoo, 2010). When the length of Jinba cuttings was 9 cm; the number of leaves, 4~6; and diameter, 3.2 mm, the length and diameter of cut flowers were longer than other cut flowers.…”
Section: Correlation Between Cultivation Methods and The Quality Of Cmentioning
confidence: 99%
“…1). Considering the finding that the more leaves, the better the above-ground part growth and rooting after planting plug seedlings (Yoo and Roh, 2009), LN is considered to be an important measure of the growth in raising plug seedlings using plug trays. The LN is the most distinct measure of growth that can be visually observed in the above-ground part.…”
Section: Ln Lw Ll and Rlmentioning
confidence: 99%
“…To make up for this deficiency, the porosity and size inside the substance are generally increased by mixing perlite. Lee et al (2020b) claimed that mountain spike speedwell did not show favorable growth in the mixed substrate of peat moss and perlite, but Yoo and Roh (2012) argued that roots of chrysanthemum 'Baekma' were long in the mixed substrate of peat moss and perlite (2:2, 3:1). Lee et al (2005) also reported that raising seedlings of Miscanthus sacchariflorus…”
Section: Seedling Growth Depending On Substrate Typementioning
confidence: 99%